2020
DOI: 10.1111/nph.16435
|View full text |Cite
|
Sign up to set email alerts
|

TubZIP28, a novel bZIP family transcription factor from Triticum urartu, and TabZIP28, its homologue from Triticum aestivum, enhance starch synthesis in wheat

Abstract: Summary Starch in wheat grain provides humans with carbohydrates and influences the quality of wheaten food. However, no transcriptional regulator of starch synthesis has been identified first in common wheat (Triticum aestivum) due to the complex genome. Here, a novel basic leucine zipper (bZIP) family transcription factor TubZIP28 was found to be preferentially expressed in the endosperm throughout grain‐filling stages in Triticum urartu, the A genome donor of common wheat. When TubZIP28 was overexpressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 72 publications
1
47
0
Order By: Relevance
“…For example, the G-box mutation in NnAGPL2a promoter may affect the binding and regulatory activity of some environmental stress responsive transcription factors in JX, such as MYC and bZIP genes [ 43 ]. In addition, G-box is also closely associated with regulation of starch biosynthesis process, for example, a previous study showed that G-box plays a role in regulation of SBE and AGPase gene expression [ 44 , 45 ]. Overall, these results partly reveal the genetic differentiation of NnAGPL2a and NnAGPS1a , and provide an important reference for identifying favored haplotype at the population level, which could be used in molecular breeding.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the G-box mutation in NnAGPL2a promoter may affect the binding and regulatory activity of some environmental stress responsive transcription factors in JX, such as MYC and bZIP genes [ 43 ]. In addition, G-box is also closely associated with regulation of starch biosynthesis process, for example, a previous study showed that G-box plays a role in regulation of SBE and AGPase gene expression [ 44 , 45 ]. Overall, these results partly reveal the genetic differentiation of NnAGPL2a and NnAGPS1a , and provide an important reference for identifying favored haplotype at the population level, which could be used in molecular breeding.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OsbZIP33 has also been inferred to play a role in regulation of starch synthesis as it is able to interact with the ACGT element buried in the promoter of SBEI and Wx (Cai et al, 2002). Recently, Song et al (2020) reported that TubZIP28 in Triticum urartu and its homolog, TabZIP28 from common wheat (Triticum aestivum), play a role in the regulation of starch synthesis as TubZIP28 binds to the promoter of cytosolic AGPase and enhances its transcription and activity. Apart from the above-mentioned regulators that directly bind to the promoters of starch synthesis-related genes to regulate their expression, some other regulators such as ZmaNAC36, ZmNAC34, rice starch regulator1 (RSR1), disulfide isomerase 1-2 protein (TaPDIL1-2), ZmMADS1a and G protein γ-subunit DEP1/qPE9-1 also have an indirect or unknown role in the regulation of starch synthesis (Fu and Xue, 2010;Zhang et al, 2014Zhang et al, , 2019aDong et al, 2019a,b;Peng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Up till now, only a few TFs that regulate starch synthesis have been identified. AP2, bZIP, and NAC TFs regulate starch synthesis related genes (SSRGs) in rice (Oryza sativa), maize (Zea mays) and wheat [11,12,[23][24][25][26][27]. For example, maize Opaque-2 (O2) indirectly represses the TF gene Prolamin-box binding factor (PBF); furthermore, O2 and PBF interact to regulate gene networks for starch and protein biosynthesis [14,27,28].…”
Section: Introductionmentioning
confidence: 99%